The Stone–Čech Compactification of Groupoids - Behrouzi, F. (Український математичний журнал, 2015)
Let G be a discrete groupoid. Consider the Stone–Čech compactification βG of G. We extend the operation on the set of composable elements G (²) of G to the operation * on a subset (βG)(²) of βG×βG such that the triple (βG, (βG)(²), *) is a compact right topological semigroupoid. Нехай G — дискретний групоїд. Розглянемо компактифікацію Стоуна-Чexa βG групоїда G. Розширимо операцію на множині G(²) єлємєнтів G, що компонуються, до операції "*" на підмножині (βG)(²) множини βG×βG такої, що трійка (βG,(βG)(²) є компактним топологічним напівгрупоїдом.